Physiotherapy Modalities and Physiotherapy Modalities and its Effect on The Development of Functional Ability in Children with Cerebral Palsyits Effect on The Development of Functional Ability in Children with Cerebral Palsy - Bambang Trisnowiyanto; Budi Utomo (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
In Indonesia, currently there are various physiotherapy intervention modalities for children with special needs, especially in cerebral palsy. The Bobath concept is a holistic approach to solving the problems of individuals with movement disorders and postural control as a result of lesions in the central nervous system. The purpose of this study was to determine the effect of physiotherapy modalities on functional abilities in children with cerebral palsy. This research was an experimental type that had a control variable with a nonequivalent control group design, but in this design the experimental group and the control group were not randomly selected, functional ability measuring tool used gross motor functional movement (GMFM). All respondents received treatment 16 times (2 times per week), measured as fisrt post-test, followed by treatment 16 times (2 times per week) measured as second post-test. The first post-test (16 times) and the second post-test (32 times), these data were compared. The results of the repeated measured ANOVA test in the control group revealed that there was a significant difference in functional ability after the bobath concept treatment (p=0.060; x1=-0.714; x2=-2.714) and after the bobath concept and taping treatment (p=0.027; x1=-2.400; x2=-6.000). But, there was found not significant after the bobath concept and stretching treatment (p =0.071; x1=-0.333; x2=-3.667), and after the bobath concept and infrared treatment (p=0.126; x1=-1.000; x2=-2.500). The results of the Freadman test there was a significant difference in functional ability after the bobath concept and massage treatment (p=0.023). The conclusion, there was a significant difference in functional ability improvement after being given treatment by the bobath concept, bobath concept plus taping, and/or bobath concept plus massage.